Oxidized LDL Modify the Human Adipocyte Phenotype to an Insulin Resistant, Proinflamatory and Proapoptotic Profile - Santiago-Fernández, Concepción; Martin-Reyes, Flores; Tome, Mónica; Ocaña-Wilhelmi, Luis; Rivas-Becerra, Jose; Tatzber, Franz; Pursch, Edith; Tinahones, Francisco J.; García-Fuentes, Eduardo; Garrido-Sánchez, Lourdes (Biomolecules (Basel, Switzerland), 2020)
Little information exists in humans on the regulation that oxidized low-density lipoprotein (oxLDL) exerts on adipocyte metabolism, which is associated with obesity and type 2 diabetes. The aim was to analyze the oxLDL effects on adipocytokine secretion and scavenger receptors (SRs) and cell death markers in human visceral adipocytes. Human differentiated adipocytes from visceral adipose tissue from non-obese and morbidly obese subjects were incubated with increasing oxLDL concentrations. mRNA expression of SRs, markers of apoptosis and autophagy, secretion of adipocytokines, and glucose uptake were analyzed. In non-obese and in morbidly obese subjects, oxLDL produced a decrease in insulin-induced glucose uptake, a significant dose-dependent increase in tumor necrosis factor-α (TNF-α), IL-6, and adiponectin secretion, and a decrease in leptin secretion. OxLDL produced a significant increase of Lox-1 and a decrease in Cxcl16 and Cl-p1 expression. The expression of Bnip3 (marker of apoptosis, necrosis and autophagy) was significantly increased and Bcl2 (antiapoptotic marker) was decreased. OxLDL could sensitize adipocytes to a lower insulin-induced glucose uptake, a more proinflammatory phenotype, and could modify the gene expression involved in apoptosis, autophagy, necrosis, and mitophagy. OxLDL can upregulate Lox-1, and this could lead to a possible amplification of proinflammatory and proapoptotic effects of oxLDL.